1998
DOI: 10.1088/0957-0233/9/11/004
|View full text |Cite
|
Sign up to set email alerts
|

A ring sensor system for the determination of volume and axis measurements of irregular objects

Abstract: In agriculture, a large variability of objects in a range of sizes and shapes is found, leading to problems in size grading. For example, for a low-cost product such as potatoes, the predominantly used mechanical size-determining systems have errors of up to 30% and can cause damage, but they are cheap and have a throughput up to 20 tonnes per hour. Alternatives which can guarantee an improvement in accuracy and a financial gain for the companies are required. In this paper methods for the determination of vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Fruit volume is calculated by summing the individual products of the cross-section areas multiplied by the helix pitch. Gall et al (1998), studying potatoes, reported CVs of less than 2.5% for tubers larger than 100 ml. Owing to the geometry of the system, errors were larger for smaller objects.…”
Section: Systems Based On Measuring the Volume Of The Gap Between Thementioning
confidence: 98%
See 1 more Smart Citation
“…Fruit volume is calculated by summing the individual products of the cross-section areas multiplied by the helix pitch. Gall et al (1998), studying potatoes, reported CVs of less than 2.5% for tubers larger than 100 ml. Owing to the geometry of the system, errors were larger for smaller objects.…”
Section: Systems Based On Measuring the Volume Of The Gap Between Thementioning
confidence: 98%
“…Another advantage of the artificial retina concept is that the photosensors used in this device are cheaper than any of the CCD or CMOS sensors equipped with video-cameras. A disadvantage of the artificial retina concept is that it cannot calculate fruit diameters, only fruit volume (Gall et al, 1998). The prototype artificial retina machine vision system developed by Kanali et al (1998) transferred the data obtained to a retina model, which was identical to the 'hardware' prototype.…”
Section: Other Techniquesmentioning
confidence: 99%
“…Finally, in regards to the repeatability test, the reason for the lower repeatability of SVol (CV = 6.1% vs. CV = 2.1% for MALS) was the above-mentioned variation of the helix pitch involved in volume computation. The intrinsic lower precision of volume measurements with respect to major axis measurements (Gall, 1997;Gall et al, 1998;Moreda et al, 2005) would play a secondary role here.…”
Section: Discussionmentioning
confidence: 95%
“…3). The algorithms used in this research are listed in Gall (1997) and Gall et al (1998). The LED's emit infrared light in sequence around the ring with one switching cycle designated a scan revolution.…”
Section: Description Of the Systemmentioning
confidence: 99%
See 1 more Smart Citation